Family history and pathogenic/likely pathogenic germline variants in prostate cancer patients. Issue 7 (24th March 2021) - Sabol, Rachel A.; Ledet, Elisa M.; Jaeger, Ellen; Hatton, Whitley; Moses, Marcus; Lankford, Anjali; Zaheria, Alexa; Barata, Pedro; Layton, Jodi L.; Lewis, Brian E.; Sartor, Oliver
Abstract: Background: Recent literature highlights the importance of germline genetic testing in prostate cancer (PCa) patients. Surprisingly, a literature review indicates that family history (FH) records are incomplete in the major published studies from prostate cancer patients. Methods: Prospective family history data were gathered from 496 men in a single institution with a personal history of PCa who underwent germline genetic testing using a panel of at least 79 genes. Comprehensive first degree FH were obtained in all PCa of patients and analysis of prevalent FH was assessed at the time of sample collection. Results: Pathogenic/likely pathogenic variants (PV/LPVs) were not associated with age at diagnosis, race, or presence of metastasis. One or more first degree relatives (FDR) with any cancer was not predictive for germline PV/LPVs for men with PCa ( p = .96). Separate analysis of patients with one or more FDR with breast, prostate, ovarian, or pancreatic cancer revealed that only FDR with breast or ovarian cancer was predictive for PV/LPVs ( p = .028, p = .015 respectively). Patients with a FDR with breast cancer had 1.8 increased risk of PV/LPVs, and patients with a FDR with ovarian cancer had 2.9 increased risk of PV/LPV. Conclusion: In men with a personal history of PCa, germline PV/LPVs were associated with a FDR with breast or ovarian cancer. Notably having FDRs with PCa does not predict for PV/LPVs. These data emphasize the contribution of FH in a data set with complete ascertainment of FH.